The scarecrow walks at midnight - Stine, R. L. (New York : Scholastic, 1994)
Jodie is staying with her grandparents on their farm and sees the scarecrows "come alive!"
"An Apple paperback."
Includes a detachable bookmark
"RL4"--P. [4] of cover
"008-012"--P. [4] of cover
540
Accelerated Reader AR
Keywords: Farm life -- Fiction; Grandparents -- Fiction; Scarecrows -- Fiction; Horror tales